Chitosan complex in the technology of feeding broiler chickens - Buyarov Viktor; Komolikova Irina; Buyarov Aleksandr; Mednova Valentina (BIO Web of Conferences, 2023)
The aim of the study was to study the effectiveness of using a domestic feed additive based on chitosan (chitosan complex KX-1). The three control houses had 118,000 chicks at the start of the experiment, and the three experimental houses had 117,906 chicks. Broilers of experienced poultry houses were injected with a chitosan complex at the rate of 70 g per 1 ton of compound feed during the entire growing period (38-40 days). In the control poultry houses, broilers received feed with nutritional value according to the VNITIP standards. It was found that the gross production of broilers for slaughter in live weight in three control poultry houses was 254,120 kg, in three experimental ones - 255,830 kg, and the production of poultry meat in slaughter weight - 193,950 kg and 197,957 kg, respectively. In poultry houses where the chitosan complex was used in feed for broiler chickens, 4007 kg (2.02%) more meat was obtained than in the control. This was achieved due to the higher viability and safety of broiler chickens in all experimental poultry houses - 93.14%, and in control - 91.83%. The superiority in feed conversion of broilers grown in experimental poultry houses in comparison with the control ones was established. The fat content in the pectoral and leg muscles of the control and experimental broilers was low - 1.42-1.12% and 3.84-3.42%, respectively. At the same time, in the pectoral and femoral muscles of the experimental broilers, the fat content was 0.30% (P<0.05) and 0.42% (P<0.05) less compared to the control ones, which indicates an increase in the dietary properties of meat with use of the chitosan complex in poultry feeding.